Implementasi Metode Problem Solving dalam Mengembangkan Berfikir Kritis Santri di Pesantren Darussholah Pusat Pakong Modung Bangkalan Madura - Masfufah; Ach. Husaini; Muji (LPPM STAI Ihyaul Ulum Gresik, 2023)
Learning is the process of learning to solve problems with experience and practice. This means that the purpose of learning activities is how to solve problems properly and quickly, both concerning knowledge, skills and attitudes, even covering all aspects of personality. One example is the BMKM (Bimbingan Membaca Kitab Kuning Mandiri) di Pondok Pesantren Darussholah Pakong Modung Bangkalan. The process of learning to teach the yellow book is certain to occur in the world of education, in the delivery of the teaching and learning process the application of the method can vary. One of the important methods found in every pesantren is problem solving. This study uses a phenomenological qualitative approach. With this type of case study. According to Moleong, naturalistic phenomenology means understanding events in relation to people in certain situations, where researchers seek to understand the meaning of a phenomenon. Meanwhile, according to Robert K.Yin, case studies are an empirical inquiry that investigates phenomena in real life contexts, the boundaries between phenomena and contexts are not clearly visible and multiple sources of evidence are used.